Analisis Perbedaan Kepuasan Konsumen Terhadap Pembelian Produk Baju Secara Online Dan Offline - Nuraini, Dewi; Evianah, Evianah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
This study aims to compare differences in customer satisfaction with the purchase of clothing products online and offline (studies on consumers online and offline in Surabaya). The sample in this study was divided into two different respondents, namely 75 respondents who bought clothes online and 75 respondents who made offline purchase of clothing products. Whereas to test the questionaire in this study must fulfill two important requirements that apply to a quastionnaire that is valid and reliable, for this reason, validitity and reliability test are used, and to answer the hypothesis proposed in this study using the Indpendent T Test statistical tool. From the result of research conducted on 75 respondents who made online purchase and 75 respondents who made offline purchase for clothing products, there were significant differences in customer satisfaction when cunsumers made purchase online and offline. This can be seen from the results of the mean for respondent satisfation online which equal to 3,997, the value is lower than the mean satisfaction of respondent offline of 4,387. This mean that consumer satisfaction of buying offline is higher than consumer satisfaction of buying online.